2020
DOI: 10.18632/oncotarget.27562
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GRK5 as a novel regulator of rhabdomyosarcoma tumor cell growth and self-renewal

Abstract: Copyright: Pham et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License 3.0 (CC BY 3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.ABSTRACT Rhabdomyosarcoma (RMS) is the most common soft-tissue pediatric sarcoma. Clinical outcomes for RMS patients with relapsed or metastatic disease remain poor. Treatment options remain limited, presenting an urgent need for novel thera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Finally, in rhabdomyosarcoma tumor cells, GRK5 has been proposed as a novel regulator of growth and self-renewal. Indeed, this kinase was able to regulate NFAT1 expression, in a kinase-independent manner, thus promoting tumor cell growth [ 104 ].…”
Section: Grk5 and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in rhabdomyosarcoma tumor cells, GRK5 has been proposed as a novel regulator of growth and self-renewal. Indeed, this kinase was able to regulate NFAT1 expression, in a kinase-independent manner, thus promoting tumor cell growth [ 104 ].…”
Section: Grk5 and Cancermentioning
confidence: 99%
“…In addition to the study of GRK5 inhibitors on cardiomyocytes, studies have explored the therapeutic potential of GRK5 inhibitors in cancer, and specifically, for the prevention of GRK5-dependent tumor progression. For example, Pham et al have demonstrated that treatment of mice with human rhabdomyosarcoma xenografts, with CCG-215022, a selective GRK5 inhibitor, resulted in a significant reduction of tumor growth [ 104 ]. Moreover, a recent study by Sommer et al investigated the effect of sunitinib, a potent small-molecule inhibitor, on GRK5 and breast cancer cells [ 122 ].…”
Section: Targeting Grk5 As a Therapeutic Strategy For Chronic-degementioning
confidence: 99%